Hemorrhagic Cystitis in a Liver Transplant Recipient Secondary to BK Virus. Issue 1 (2017) - Kamal, Faisal; Ali, Bilal; Barnes, Matthew; Kamal, Sehrish; Nair, Satheesh; Gonzalez, Humberto
ABSTRACT : N/A: The association between BK virus infection and hemorrhagic cystitis (HC) in hematopoietic stem cell transplant (HSCT) recipients is well established. However, BK virus‐associated HC has not been described in liver transplant (LT) recipients. We present a case of BK virus‐associated HC in a LT recipient. Our patient presented with worsening liver function tests 2 years after transplantation and was found to have acute cellular rejection. He was treated with increased immunosuppression and subsequently developed hematuria. He was eventually diagnosed with BK virus‐associated HC.